Case report: Genomic analysis of a therapy-related chronic myelomonocytic leukemia with KMT2A rearrangement that progressed to acute myeloid leukemia with acute promyelocytic leukemia-like features - Suzuki, Tomotaka; Yokomori, Rui; Sanda, Takaomi; Kikuchi, Takaki; Marumo, Yoshiaki; Kinoshita, Shiori; Narita, Tomoko; Masaki, Ayako; Ito, Asahi; Ri, Masaki; Kusumoto, Shigeru; Komatsu, Hirokazu; et al. (Frontiers in Oncology, 2023)
We report a 69-year-old female who was a human T-cell leukemia virus type 1 carrier and exhibited a unique clinical course of developing three hematological malignancies within a short period: diffuse large B-cell lymphoma (DLBCL), chronic myelomonocytic leukemia (CMMoL), and acute myeloid leukemia (AML). Although the blast cells in AML showed typical morphological and immunophenotypical features of acute promyelocytic leukemia (APL), it did not harbor RARA gene fusion and thus initially diagnosed as APL-like leukemia (APLL). The patient developed heart failure with a fulminant clinical course and died soon after the diagnosis of APLL. Retrospective analysis with whole-genome sequencing detected a chromosomal rearrangement between KMT2A and ACTN4 gene loci both in CMMoL and APLL samples, but not in the DLBCL sample. Therefore, CMMoL and APLL were considered to be derived from the same clone with KMT2A translocation associated with prior immunochemotherapy. However, KMT2A rearrangement is rarely found in CMMoL in general and ACTN4 is also a rare partner of KMT2A translocation. Thus, this case did not follow typical transformational process of CMMoL or KMT2A-rearranged leukemia. Importantly, additional genetic alterations, including NRAS G12 mutation, were found in APLL, but not in CMMoL samples, suggesting that they might contribute to leukemic transformation. This report highlights the diverse effects of KMT2A translocation and NRAS mutation on the transformation of hematological cells as well as the importance of upfront sequencing analysis to detect genetic backgrounds for a better understanding of therapy-related leukemia.